PENGETAHUAN PASIEN TENTANG UPAYA PENCEGAHAN STROKE DENGAN TERAPI NON-FARMAKOLOGI DI POLI DALAM RSU DR. SLAMET GARUT - Theresia Eriyani; Iwan Shalahuddin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Hypertension that occurs for years can cause various problems. Effort to measure blood pressure regularly and treat it effectively, aim to prevent complications. Someone who usually smoke and let high cholesterol levels in the blood more at risk of complications. One of the complications caused by hypertension is stroke, so it is necessary to control the hypertensive patients because hypertension control can be the key prevention of stroke. This study aims to find out how the knowledge of hypertensive patients about stroke prevention efforts by way of non-pharmacologic therapy, Non-pharmacological therapies here include regular exercise, low-salt diet and lifestyle changes.The type of research is descriptive research, the polpulation in this study is all hypertensive patients who come to the Poly In dr. Slamet Garut in August 2012. The sample in this research using non probability method with accidental sampling with 25 samples. Obtained that the knowledge of hypertensive patients about the effort of stroke prevention by non-pharmacological therapy in Poli In dr. Slamet Garut from 25 respondents, have the best knowledge as much as 28.00%, knowledge enough 36.00%, have knowledge less 36.00%.Most of the respondents who studied about the knowledge of hypertensive patients about stroke prevention efforts by non-pharmacological therapy in Inner Polyclinic dr. Slamet Garut has less knowledge and enough knowledge respectively that is 36.00% (9 persons).